Suppression of cancer stemness by upregulating Ligand-of-Numb protein X1 in colorectal carcinoma. - Lin Ma (PLoS ONE, 2017)
Cancer stem-like cells (CSCs) have been reported to play major roles in tumorigenesis, tumor relapse, and metastasis after therapy against colorectal carcinoma (CRC). Therefore, identification of colorectal CSC regulators could provide promising targets for CRC. Ligand-of-Numb protein X1 (LNX1) is one E3 ubiquitin ligase which mediates the ubiquitination and degradation of Numb. Although several studies indicate LNX1 could be a potential suppressor of cancer diseases, the functions of LNX1 in mediating cancer stemness remain poorly understood. In this study, LNX1 was identified as a negative regulator of cancer stemness in CRC, which was downregulated in colonospheres or side population (SP) cells. Furthermore, the coxsackievirus and adenovirus receptor (CXADR) was found to be one critical downstream mediator of cancer stemness regulated by LNX1. Interestingly, the anti-breast cancer drug tamoxifen was found to be an agonist of LNX1 and suppress cancer stemness in CRC. In sum, this study provided the evidences that LNX1 signaling plays important roles in regulating the stemness of colon cancer cells.